2015
DOI: 10.1093/mnrasl/slv129
|View full text |Cite
|
Sign up to set email alerts
|

Type Ia supernovae with bimodal explosions are common – possible smoking gun for direct collisions of white dwarfs

Abstract: We discover clear doubly-peaked line profiles in 3 out of ∼ 20 type Ia supernovae (SNe Ia) with high-quality nebular-phase spectra. The profiles are consistently present in three well-separated Co/Fe emission features. The two peaks are respectively blueshifted and red-shifted relative to the host galaxies and are separated by ∼ 5000km/s. The doubly-peaked profiles directly reflect a bi-modal velocity distribution of the radioactive 56 Ni in the ejecta that powers the emission of these SNe. Due to their random… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
114
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(119 citation statements)
references
References 30 publications
4
114
1
Order By: Relevance
“…These will allow comparisons to the peculiar latetime photospheric spectra of SNe Iax. Furthermore, our newly-proposed long-lived radiation source at the center of SN Ia ejecta may have some connection to some of the persistent puzzles of late-time SN Ia spectra, including the existence of bimodal line profiles (Dong et al 2015). This previously unconsidered source of radiation will also affect the ionization balance within the SN Ia ejecta, which may alter inferred mass estimates of stable 54 Fe and 58 Ni (Mazzali et al 2015).…”
Section: Discussionmentioning
confidence: 84%
“…These will allow comparisons to the peculiar latetime photospheric spectra of SNe Iax. Furthermore, our newly-proposed long-lived radiation source at the center of SN Ia ejecta may have some connection to some of the persistent puzzles of late-time SN Ia spectra, including the existence of bimodal line profiles (Dong et al 2015). This previously unconsidered source of radiation will also affect the ionization balance within the SN Ia ejecta, which may alter inferred mass estimates of stable 54 Fe and 58 Ni (Mazzali et al 2015).…”
Section: Discussionmentioning
confidence: 84%
“…For instance, Sasdelli et al (2017) tried to classify explosion mechanisms based on their predicted spectra and found that, while all mechanisms had shortcomings, equalmass violent mergers fit 91bg-like SNeIa quite well, while detonations of sub-Chandrasekhar white dwarfs and delayed detonations better represented normal SNeIa. From the distribution of inferred 56 Ni masses, Piro et al (2014) suggested that normal and 91bg-like SNeIa might arise from the double-detonation (Livne 1990) and direct-collision (Dong et al 2015) scenarios, respectively. In contrast, e.g., Graur et al (2017) suggested a common origin on statistical grounds: while 91bg-like SNeIa are preferentially found in massive galaxies, they seem to "cut into the share" of the normal SNeIa.…”
Section: Introductionmentioning
confidence: 99%
“…Mazeh & Shaham 1979;Kiseleva et al 1998;Fabrycky & Tremaine 2007;Dong et al 2013;Wu & Murray 2003;Ford et al 2000;Katz et al 2011;Socrates et al 2012;Dawson et al 2015). It has also been recently realized that the rate for mergers and collisions of white-dwarfs (WDs) can be significantly enhanced in field triple systems (Thompson 2011;) and quadrupole systems (Pejcha et al 2013), and WD collisions in triples may be responsible for the majority of type Ia supernovae Kushnir et al 2013;Dong et al 2015).…”
mentioning
confidence: 99%